RELAKSASI DAN TERAPI MENULIS EKSPRESIF SEBAGAI PENANGANAN KECEMASAN PADA DIFABEL DAKSA - Rohmadani, Zahro Varisna (Universitas 'Aisyiyah Yogyakarta, 2017)
Abstract: This study aims to determine the effectiveness of treatment in the form of muscle relaxation and emosional experience expressive writing therapy to reduce anxiety on the physically disabled people. The subjects were 8 students Balai Besar Rehabilitasi Sosial Bina Daksa. The subjects to be addressed such as muscle relaxation and expressive writing therapy. Data analysis method used is nonparametric statistical techniques by using Wilcoxon Signed Rank Test to test for differences in anxiety scores of the subject group pretest and posttest. Wilcoxon Signed Rank Test results showed that muscle relaxation therapy and expressive writing therapy in lowering anxiety with p=0.012.Keywords: muscle relaxation, expressive writing therapy, anxiety, physically disabled people